Secret in their eyes [videorecording (Blu-Ray + DVD)] - Kauderer, Emilio (Universal Studios Home Entertainment, 2016)
A tight-knit team of rising investigators, along with their supervisor, is suddenly torn apart when they discover that one of their own teenage daughters has been brutally murdered.